Soil type determines the magnitude of soil fertility changes by forest-to-pasture conversion in Western Amazonia - Rocha, Fernando Igne; Jesus, Ederson da Conceição; Teixeira, Wenceslau Geraldes; Lumbreras, José Francisco; Clemente, Eliane de Paula; da Motta, Paulo Emilio Ferreira; Borsanelli, Ana Carolina; Dutra, Iveraldo dos Santos [UNESP]; de Oliveira, Aline Pacobahyba (Elsevier, 2023)
The deforestation of tropical forests raises environmental concerns worldwide. Removing the pristine forest impacts the soil, consequently affecting the environmental services it provides. Within this context, the main goal of this study was to determine how the conversion of the tropical rainforest to pasture affects soil fertility across an extended range of soil heterogeneity, including different soil types. We sampled 13 sites, among forests, recent pastures (≤7-year-old), and old pastures (≥10-year-old), on Acrisols, Ferralsols, Plinthosols, and Luvisols, across a ± 800 km geographical range in the Western Brazilian Amazon. Soils were classified taxonomically, and their superficial layer's chemical and physical properties (0–10 cm) were analyzed. Furthermore, we tested the sensibility of Actinobacteria and Proteobacteria to detect changes in these soil properties based on their ecological habitat. An inter-regional gradient of soil fertility was observed, and the sampling sites were clustered mostly by soil type and associated land use than by spatial distance. The Sum of bases, Ca + Mg, base saturation, Al saturation, and pH were consistently affected by land use, increasing after conversion to pasture, at different degrees and with a more pronounced effect on oxidic soils. The Sum of bases was the only property that increased significantly among the study sites (Radj = 0.860, p < 0.001), being able to detect the effect of anthropic land use on a larger coverage of soil types. Finally, the Actinobacteria:Proteobacteria ratio was also sensitive to the impact of forest-to-pasture conversion, with a higher ratio observed in pasture systems, and it was positively correlated with soil pH (rho = 0.469, p < 0.001). Our results consistently show that the forest-to-pasture conversion leads to strong alterations in the soil environment, with varying intensities depending on soil type.
Keywords: Amazonia; Bioindicator; Deforestation; Land clearing; Land-use change; Pedodiversity